Antimicrobial and cytotoxic activities of the leaves extracts of dissochaeta gracilis - Abd Rahman, Azizah; Bakhtiar, M. Taher (2014)
Plants are important sources of natural product that are widely used as herbal medicine because it is known to be effective with less unwanted side effects. Dissochaetagracilis which also known as ‘Senduduk’ or ‘Cong Keradak was found to be pharmacologically unexplored and the research was conducted as the thought it is worthwhile to explore it’s potential value. The extraction has been carried out by using soxhlet extraction method with solvent n-Hexane, dichloromethane, and methanol successively. The antimicrobial activities of plant extracts were tested against various microbes which were two Gram-positive bacteria namely Staphylococcus aureus, and Bacillus cereus, two Gram-negative bacteria namely Pseudomonas aeruginosa and Escherichia coli and two fungi consist of Candida albicans and Aspergillus spp. Based on the antimicrobial susceptibility result, the disc diffusion test showed that methanol crude extract of leaves of D. gracilis inhibit the growth of B. cereus, S. aureus, and P.aeruginosa with zone inhibition measured at 13.67±0.58, 12.33±1.53, and 10.33±0.58, respectively. Meanwhile, the n-Hexane, and DCM extracts of D. gracilis showed no antimicrobial activity against all microorganisms tested in this study. The minimum inhibitory concentration (MIC) values of methanol extract for B. cereus, S. aureus, and P. aeruginosawere 6.25, 12.5, and 25.0 mg/mL, respectively. The result obtained from minimum bactericidal concentration (MBC) showed that the methanol extract enable to kill the growth of B.cereus at 12.5 mg/mL, S. aureus at 25 mg/mL and P. aeruginosa at 50 mg/mL. In conclusion, D. gracilis have a potential to be a good antimicrobial agent against some pathogenic strains of microorganisms and thus further investigation need to be done before it can successfully be used to treat certain infectious disease that infect the human.